La place des scientifiques dans un processus de gestion intégrée des zones côtières : évaluation des pressions polluantes d’origine terrestre sur la baie du Robert (Martinique) - Anne Rizand; P. Mariel; K. Pinte (VertigO)
Located in the French West Indies, Martinique is a small volcanic island characterized by numerous remarkable marine ecosystems. This island is also under various anthropogenic pressures which exert a continuous pressure on the environment. These pressures are increased along the coast which concentrates the whole stakes of sustainable development concept.Third city of Martinique, Le Robert is a new urban center which has to be watchful towards its natural environment and mainly its bay.Therefore, the city came into a process of Integrated Coastal Zone Management (ICZM), since 2006 with several scientific partners. Two main stakes are taken into account: eutrophication and chemical diffusion damage, and above all sedimentation. Indeed, the silting up of the bay is speeding up, and reduces spaces herbarium can colonize. The first step of this approach was the characterization of the Robert coastal “eco-socio-system” by actors, which one did not, at least at the beginning, involve themselves at the same rythm neither level.The researchers tried to answer very specifically to the administrator expectations trying to be both actor and mediator in the ICZM. The environmental indicators allowed us to make an inventory of the diffuse pollutions affecting the watershed and provided first decision making-aid tools for the local executives.The economic and social scientific team is focusing its work on the perception of the ICZM by a key group of local actors: the fishermen. On this issue, i.e. the appropriation of ICZM approach by the different local actors, we have to make specific efforts to integrate those results for the sustainable management of the bay and to co-build adapted planning tools.